Textural and geochemical characteristics of beach sands along the western Gulf of Mexico, Mexico - Hernández-Hinojosa, V.; Montiel-García, P.; Armstrong-Altrin, J.; Ramasamy, Nagarajan; Kasper-Zubillaga, J. (Universitatea de Nord din Baia Mare, 2018)
The beach areas Esmeralda (EM) and La Mancha (LM) are located in the western part of the Gulf of Mexico. Here we studied the textural, petrological, and geochemical variations between the EM and LM beach sands to infer their provenance. The texture and petrographic analyzes indicated that the EM sands are fine-grained in size and abundant in quartz content. The SEM-EDS data revealed that the EM sands are abundant in heavy minerals like ilmenite and LM sands are enriched in zircon. SiO2 content is higher in EM sand than in LM sand. The chemical index of alteration (CIA) revealed that the intensity of weathering in the beach areas was similar, varying from low to moderate. The chondrite normalized rare earth element (REE) patterns with negative Eu anomaly of the EM sands indicated a felsic provenance, whereas the absence of negative europium anomaly in the LM sands indicated its derivation from intermediate source rocks like andesite. The major element based multidimensional tectonic discrimination diagrams suggested a passive margin setting for the sediments from both beach areas. The compositional differences identified between the EM and LM beach areas suggested that longshore currents in the mixing and homogenization of sands are not significant.